2011
DOI: 10.4161/hv.7.2.14068
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of a tetravalent meningococcal serogroups A, C, W-135 and Y conjugate vaccine in adolescents and adults

Abstract: The highest incidence of invasive meningococcal disease is in young children, with a second peak in adolescents/young adults. All five major disease-causing serogroups (A, B, C, W-135 and Y) have been described in Asia. Immunogenicity and safety of the investigational meningococcal ACWY-tetanus toxoid conjugate vaccine (ACWY-TT, GlaxoSmithKline Biologicals) was evaluated in healthy, meningococcal conjugate vaccine-naïve adolescents in the Philippines, India and Taiwan. 1025 adolescents were randomized (3:1) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 26 publications
10
82
1
1
Order By: Relevance
“…Similar results have also been demonstrated in studies conducted in Asia and continental Europe which compared a quadrivalent tetanus toxoid conjugate meningococcal vaccine and MenACWY-PS (16)(17)(18). The differences seen in the current study may relate to geographical variations in meningococcal nasopharyngeal carriage between the United Kingdom study population and those from previous studies leading to differential degrees of natural priming or may be due to differences in the comparator polysaccharide vaccine used.…”
Section: Discussionsupporting
confidence: 73%
“…Similar results have also been demonstrated in studies conducted in Asia and continental Europe which compared a quadrivalent tetanus toxoid conjugate meningococcal vaccine and MenACWY-PS (16)(17)(18). The differences seen in the current study may relate to geographical variations in meningococcal nasopharyngeal carriage between the United Kingdom study population and those from previous studies leading to differential degrees of natural priming or may be due to differences in the comparator polysaccharide vaccine used.…”
Section: Discussionsupporting
confidence: 73%
“…The safety profile of MenACWY-TT was comparable to that observed in previous studies conducted with adolescents and young adults (42,43). However, a lower incidence of pain at the injection site was observed in two other studies, one conducted with adolescents from India, Taiwan, and the Philippines (26.2%) (44) and the other with adults from Lebanon and the Philippines (19.4%) (36). It is possible that the lower incidence of pain observed in the two latter studies reflects cultural differences in the reporting of symptoms.…”
Section: Discussionsupporting
confidence: 60%
“…Vaccine response was non-inferior to MenACWY PS and the post-vaccination rSBA GMT against all serogroups were statistically significantly higher following MenACWY-TT versus MenACWY-PS vaccine after one month. 54 Another study including 225 adolescents from Philippines and Saudi Arabia also showed noninferiority in the immunologic response to MenACWY-TT compared to the PS vaccine. 55 Berry et al studied the role of O-acetylation of serogroup APS antigenic epitopes in humans and mice and demonstrated that serum bactericidal titers following immunization with de-O-acetylated (de-O-Ac) conjugate vaccine were at least 32-fold lower than those following immunization with O-Ac PS-conjugate vaccine.…”
Section: Immunogenicity Of Menacwy-ttmentioning
confidence: 96%